A Randomized Controlled Trial on Zinc Supplementation for Prevention of Acute Respiratory Infections in Infants : Zinc Supplementation for Prevention of ARI - Khan, Arshad; Anwar, Hamayun; Farhat, Anila; Ahmed, Ajaz; Khan, Irfan; Ullah, Irfan (Pakistan Journal of Health Sciences, 2023)
There is little evidence that zinc supplementation will be effective in treating acute respiratory infection (ARI), but it may prevent respiratory infections when taken in conjunction with antibiotics. Objective: To assess the zinc supplementation for acute respiratory infection prevention in infants. Methods: A randomized controlled trail was conducted on 120 acute respiratory infected infants in Pediatric Unit, Qazi Hussain Ahmad Medical Complex, Nowshera from 1st January 2022 to 30th June 2022. Infants having 6-14 months of age with acute respiratory infections were enrolled. Infants were allocated to two groups: Group-I infants receiving Zinc (20 mg/5 mL) in terms of Zinc sulphate (N=60) and Group-II infants taking syrup (Placebo) (N=60). Results: Of the total 220 episodes, the frequency of episodes in zinc and placebo group was 106 and 114 respectively, accounting for 7.78 and 8.68 per child year after 5 months. Based on GEE regression model observed an insignificant decrease of 8% (Adjusted IRR 0.89, 95% CI 0.79-1.01) in episodes of acute respiratory infections in zinc group as compared to placebo group. However, acute respiratory infections episodes (Adjusted IRR 0.36, 95% CI: 0.25-0.35) decreased by 60% in zinc group. Zinc supplementation reduced the acute respiratory days significantly by 14% (Adjusted RR 0.83, 95% CI: 0.76-0.92). Conclusions: Prophylactic zinc supplementation for two weeks decreased acute lower respiratory tract infection morbidity in apparently healthy infants and improved the infant’s recovery from acute respiratory infections and reduced their hospitalization as compared to placebo group